Formation of children's neighborhood spaces: Between everyday life and freedom - Erza Rahma Hajaty; Antony Sihombing; Evawani Ellisa (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Ideally, children interact in spaces that have been provided with physical conditions that are comfortable and safe for children. However, children can have the will to determine the interaction spaces they like. So it is necessary to find out how the children's neighborhood forms an interaction space and where their preferred position is. This study uses a qualitative method with a grounded theory approach located in one of the settlements in Kabupaten Bogor, Jawa Barat, Indonesia. The results of the study show that children in determining interaction spaces are motivated by everyday life which includes responsibilities, preferred activities, and gathering activities; as well as freedom which includes freedom to consume time and freedom to consume space. Preferred positions in interaction spaces are around the bandminton court and along the edge of the park. This research is useful for architects so they can design each side of the space as a possibility to become an interaction space that is in accordance with the thoughts and desires of children. This study is also useful to be able to increase the level of the children's neighborhood.